Gene expression and signaling in Rxo1 governed innate immunity in cereals - Seck, Amadou (Kansas State University, 2008)
Many maize lines carry Rxo1, an NB-LRR gene that confers a rapid hypersensitive response (HR) after infiltration with the rice streak pathogen Xanthomonas oryzae pv. oryzicola (Xoc) or the maize stripe pathogen Burkholderia andropogonis (Ba) carrying the effector genes avrRxo1 or avrRba1 respectively. Interestingly, when expressed as a transgene in rice, Rxo1 also confers a strong and rapid HR to Xoc strains harboring the avrRxo1 type III effector gene. To gain insights into the Rxo1 signaling network, we used a combination of functional genomics and bioinformatics, molecular genetics and reverse genetics. Microarray experiments were carried out to investigate the temporal expression profiles of nonhost and host responses to isogenic strains of Xanthomonas oryzae pv. oryzae (Xoo), the rice bacterial blight pathogen, and Ba with and without the Xoc type III secreted effector gene avrRxo1. Xoc AvrRxo1 induces disease resistance in maize when delivered by Xoo or Ba. We show that recognition of the two bacterial pathogens is translated into similar transcriptional outputs. Cluster analyses revealed that Xoo and Ba co-regulated genes display different kinetics and amplitudes and showed that gene clusters are associated with overrepresentation of known and putative novel DNA cis regulatory elements. One early induced gene, ZmPti1b, is a serine threonine kinase. RNAi-mediated gene silencing of a rice ortholog of ZmPti1b, OsPti1a, revealed that OsPti1a is required for Rxo1-governed resistance. Using a full length coding sequence as bait to screen a yeast-two-hybrid library, we identified 11 rice proteins that interact with RXO1. Functional analysis of two showed that Os1PVOZ, encoding a putative transcription factor, is required for Rxo1-dependent HR whereas OsATL6, a putative RING finger type E3 ubiquitin ligase gene is dispensable. Scanning of the rice genome for putative DNA binding sites suggests that Os1PVOZ is a master regulator of many signal transduction pathways, including those that mediate plant defense responses. Our investigations identified key signaling components that mediate Rxo1-specified resistance and possibly resistance mediated by other R genes.
Keywords: Signal; Transduction; Agriculture, Plant Pathology (0480)